2016
DOI: 10.1188/16.cjon.e34-e40
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Massage During Chemotherapy and/or Biotherapy Infusions: Patient Perceptions of Pain, Fatigue, Nausea, Anxiety, and Satisfaction

Abstract: Participants (N = 58) reported a statistically significant reduction in each of the following variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…The short-term anxiety reduction found in our study is also similar to extant research [18]. Mean pre-OM anxiety scores were relatively low, which were similar to other studies which measured anxiety on the same 0 to 10 point scale in samples of cancer outpatients (2.56 in those receiving chemotherapy and/or biotherapy [39] and 3.36 in those at a cancer resource center) [23]. The current research, however, studied the effect of OM on anxiety in a much larger, more diverse retrospective sample than extant studies.…”
Section: Discussionsupporting
confidence: 90%
“…The short-term anxiety reduction found in our study is also similar to extant research [18]. Mean pre-OM anxiety scores were relatively low, which were similar to other studies which measured anxiety on the same 0 to 10 point scale in samples of cancer outpatients (2.56 in those receiving chemotherapy and/or biotherapy [39] and 3.36 in those at a cancer resource center) [23]. The current research, however, studied the effect of OM on anxiety in a much larger, more diverse retrospective sample than extant studies.…”
Section: Discussionsupporting
confidence: 90%
“…Prior studies have reported benefits of massage therapy in the pediatric inpatient cancer population, 1,10 in patients with solid tumors, 24 in postoperative cancer patients, 8 in the outpatient oncology clinical setting, 3,4,12 and in patients actively undergoing bone marrow transplant (BMT) treatment. 13 In contrast, this study focuses on studying the effects of massage therapy on all adult BMT inpatients irrespective of the timing of their BMT therapy.…”
Section: Introductionmentioning
confidence: 99%
“…A total review of 15 studies that related to nursing outcomes to alleviate physical discomfort for cancer patients receiving chemotherapy is shown in Table 1. Gilmour F, et al 8 Kruse M, et al 9 Ferreira EB, et al 10 Albusoul RM, et al 11 Hsu HT, et al 12 Jacobs JM, et al 13 Zalina Abu, et al 14 Robison JG, et al 15 Backman M, et al 16 Coelho A, et al 17 Park R, et al 18 Devi ES, et al 19 Mollaoğlu M, et al 20 Karagozoglu S, et al 21 Griffiths…”
Section: Methodsmentioning
confidence: 99%